Lipopolysaccharide detection by the innate immune system may be an uncommon defence strategy used in nature - Anna E. Gauthier; Randi D. Rotjan; Jonathan C. Kagan (Open Biology, 2022)
Since the publication of the Janeway's Pattern Recognition hypothesis in 1989, study of pathogen-associated molecular patterns (PAMPs) and their immuno-stimulatory activities has accelerated. Most studies in this area have been conducted in model organisms, which leaves many open questions about the universality of PAMP biology across living systems. Mammals have evolved multiple proteins that operate as receptors for the PAMP lipopolysaccharide (LPS) from Gram-negative bacteria, but LPS is not immuno-stimulatory in all eukaryotes. In this review, we examine the history of LPS as a PAMP in mammals, recent data on LPS structure and its ability to activate mammalian innate immune receptors, and how these activities compare across commonly studied eukaryotes. We discuss why LPS may have evolved to be immuno-stimulatory in some eukaryotes but not others and propose two hypotheses about the evolution of PAMP structure based on the ecology and environmental context of the organism in question. Understanding PAMP structures and stimulatory mechanisms across multi-cellular life will provide insights into the evolutionary origins of innate immunity and may lead to the discovery of new PAMP variations of scientific and therapeutic interest.